BATERAI CERDAS DARI ELEKTROLIT POLIMER KITOSAN-PVA DENGAN PENAMBAHAN AMONIUM NITRAT - Bambang Riyanto; Akhiruddin Maddu; Ratna Sari Dewi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Batteries are practical and inexpensive source of energy. Avariety of new battery material technology continue to be developed, along with the demands of green technology. Chitosan is a biopolymer, non-toxic, and the nitrogen atom in the amine and hydroxyl group has free electron, so that can be used as an electrolyte polymer which has good ionic conductivity and can be fabricated as batteries. The purpose of this study was to determine the characteristics of polymer electrolyte chitosan-PVA batteries with addition of ammonium nitrate. The best material formulation obtained of polymer electrolyte made from 40 wt% chitosan, 60 wt% PVA, and 6% glutaraldehida. SEM showed that the polymer electrolyte formed was very homogeneous. X-ray diffraction (XRD) showed an amorphous structure. The ion conductivity tends to increased along with the increasing of added ammonium nitrate. The conductivity value obtained was 2.2 x 10 -5 S cm for the sample by addition ammonium nitrate 35 wt%. Chitosan-PVA based battery has voltage 0.95 V, electric current 0.7 mA, and can show a color fading along with decreasing battery power. With this character it can be developed as smart battery. Key words: battery, chitosan, ion conductivity, polymer electrolyte